Phylogenetic and virulence analysis of tick-borne encephalitis viruses from Japan and far-eastern Russia - Hayasaka, Daisuke; Suzuki, Yoshiyuki; Kariwa, Hiroaki; Ivanov, Leonid; Volkov, Vladimir; Demenev, Vladimir; Mizutani, Tetsuya; Gojobori, Takashi; Takashima, Ikuo (Journal of General Virology, 1999)
We have previously reported that tick-borne encephalitis (TBE) is endemic in a specific area of Hokkaido, Japan. In Oshima, the southern part of Hokkaido, TBE virus was isolated from sentinel dogs, ticks and rodents in 1995 and 1996. To identify when these TBE viruses emerged in Hokkaido, the times of divergence of TBE virus strains isolated in Oshima and far-eastern Russia were estimated. TBE virus was isolated in Khabarovsk in 1998 and the nucleotide sequences of viral envelope protein genes of isolates from Oshima and Khabarovsk were compared. From the synonymous substitution rate of these virus strains, the lineage divergence time of these TBE virus strains was predicted phylogenetically to be about 260–430 years ago. Furthermore, the virulence of TBE virus isolates from Oshima and Khabarovsk were compared in a mouse model. The results showed that the isolates possessed very similar virulence in mice. This report provides evidence that the Oshima strains of TBE virus in Hokkaido emerged from far-eastern Russia a few hundred years ago and this explains why these strains possess virulence similar to the TBE viruses isolated in Russia.